Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's determine the inverse function [tex]\( f^{-1}(x) \)[/tex] for the given function [tex]\( f(x) = 10^x \)[/tex].
### Step-by-Step Solution:
1. Start with the given function:
[tex]\[ f(x) = 10^x \][/tex]
2. To find the inverse, we need to express [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]. First, replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = 10^x \][/tex]
3. Now, we need to solve for [tex]\( x \)[/tex]. To do this, we take the logarithm of both sides. Since our function is exponential with base 10, we use the common logarithm (logarithm base 10):
[tex]\[ \log(y) = \log(10^x) \][/tex]
4. Using the properties of logarithms, specifically that [tex]\( \log(a^b) = b\log(a) \)[/tex], we get:
[tex]\[ \log(y) = x \cdot \log(10) \][/tex]
5. Since [tex]\( \log(10) = 1 \)[/tex]:
[tex]\[ \log(y) = x \cdot 1 \][/tex]
Therefore,
[tex]\[ \log(y) = x \][/tex]
6. Now, solve for [tex]\( x \)[/tex]:
[tex]\[ x = \log(y) \][/tex]
7. Replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] to express the inverse function:
[tex]\[ f^{-1}(x) = \log(x) \][/tex]
Thus, the inverse function [tex]\( f^{-1}(x) \)[/tex] for the given function [tex]\( f(x) = 10^x \)[/tex] is:
[tex]\[ f^{-1}(x) = \log(x) \][/tex]
So, the result is:
[tex]\[ f^{-1}(x) = \log_{10}(x) \][/tex]
### Step-by-Step Solution:
1. Start with the given function:
[tex]\[ f(x) = 10^x \][/tex]
2. To find the inverse, we need to express [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]. First, replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = 10^x \][/tex]
3. Now, we need to solve for [tex]\( x \)[/tex]. To do this, we take the logarithm of both sides. Since our function is exponential with base 10, we use the common logarithm (logarithm base 10):
[tex]\[ \log(y) = \log(10^x) \][/tex]
4. Using the properties of logarithms, specifically that [tex]\( \log(a^b) = b\log(a) \)[/tex], we get:
[tex]\[ \log(y) = x \cdot \log(10) \][/tex]
5. Since [tex]\( \log(10) = 1 \)[/tex]:
[tex]\[ \log(y) = x \cdot 1 \][/tex]
Therefore,
[tex]\[ \log(y) = x \][/tex]
6. Now, solve for [tex]\( x \)[/tex]:
[tex]\[ x = \log(y) \][/tex]
7. Replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] to express the inverse function:
[tex]\[ f^{-1}(x) = \log(x) \][/tex]
Thus, the inverse function [tex]\( f^{-1}(x) \)[/tex] for the given function [tex]\( f(x) = 10^x \)[/tex] is:
[tex]\[ f^{-1}(x) = \log(x) \][/tex]
So, the result is:
[tex]\[ f^{-1}(x) = \log_{10}(x) \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.